Identification and treatment of comorbidity in patients with rheumatoid arthritis. (October 2013) - Kelly, Clive; Malik, Saadia; Barnes, Jonathan; Gertig, Helen; Hamilton, Jennifer
Life expectancy has been notably reduced in patients with rheumatoid arthritis (RA) since the disease was first characterized, but the causes of death and disability are changing and survival appears to be improving. This review article discusses the evolving pattern of morbidity and mortality in RA and reviews the evidence base for the identification and treatment of each of the major categories of system involvement. We also address the increasing burden of sepsis in RA, and discuss the relationship of RA to both malignant disease and osteoporosis. We conclude with the assessment of fatigue – an often neglected aspect of RA. We evaluate the contribution of drug therapy both in contributing to and treating comorbidity in RA, and offer clinical guidance on how to maximize patient benefit from early identification and intervention.